Estimation and forecasting in large datasets with conditionally heteroskedastic dynamic common factors - Lucia Alessi; Matteo Barigozzi; Marco Capasso (European Central Bank (ECB), 2009)
We propose a new method for multivariate forecasting which combines Dynamic Factor and multivariate GARCH models. The information contained in large datasets is captured by few dynamic common factors, which we assume being conditionally heteroskedastic. After presenting the model, we propose a multi-step estimation technique which combines asymptotic principal components and multivariate GARCH. We also prove consistency of the estimated conditional covariances. We present simulation results in order to assess the finite sample properties of the estimation technique. Finally, we carry out two empirical applications respectively on macroeconomic series, with a particular focus on different measures of inflation, and on financial asset returns. Our model outperforms the benchmarks in fore-casting the inflation level, its conditional variance and the volatility of returns. Moreover, we are able to predict all the conditional covariances among the observable series.
Keywords: C52; C53; 330; Conditional Covariance; Dynamic Factor Models; Inflation forecasting; multivariate GARCH; Volatility Forecasting; Prognoseverfahren; Inflation; Volatilität; ARCH-Modell; Faktorenanalyse; Modellierung